Awake emergency endotracheal intubation using sheath-assisted technique for patients having malignant tracheal stenosis under fluoroscopy guidance: a retrospective study. (April 2017) - Jiao, Dechao; Han, Xinwei; Wu, Gang; Ren, Jianzhuang; Li, Zhen; Wang, Ling
Background: For patients having a severe larynx or tracheal stenosis, emergency endotracheal intubation (EEI) may be needed due to respiratory failure. Purpose: To evaluate the feasibility and effectiveness of awake EEI using a fluoroscopy-guided sheath-assisted technique for adult patients having a malignant tracheal stenosis. Material and Methods: From October 2009 to May 2015, 219 patients having a malignant tracheal stenosis causing dyspnea or asphyxia required EEI. Of these, 32 patients who experienced intubation difficulties or failure were included in this study. Data on the technical success, procedure time, complications, and clinical outcome were collected. The pulse oxygen saturation (SpO2 ) and Hugh-Jones classification were used to evaluate the respiratory function before and after EEI. Results: Awake fluoroscopy-guided EEI was technically successful in 15 ± 4 min and acute dyspnea was resolved in all patients. The SpO2 and Hugh-Jones classification increased after EEI ( P  < 0.05). Subsequent treatments included tracheal stents (n = 15), surgical resection (n = 10), and palliative tracheotomy (n = 7), which were performed within 72 h after EEI. Conclusion: Awake EEI using a sheath-assisted technique for adult patients having a malignant tracheal stenosis is a safe and effective procedure.